Synthesis and biological evaluation of enantiopure substituted titanocene complexes - Cini, Melchior (2015)
Tolerated by normal tissues, implementation of anti-cancer therapies based on titanium compounds is limited by low efficacy/selectivity, lack of understanding of their mode(s) of action and access to the most active chiral variants. This thesis reports the synthesis, characterization and biological evaluation of a novel class of chiral substituted titanocenes from novel chiral cyclopentadienyl ligands, themselves accessible from substituted pentafulvenes. After an introductory chapter, the second chapter describes the synthesis and biological evaluation of substituted (rac/meso)-mixtures of TiCl2{η- C5H4CHEt(phenyl)}2 (abbreviated CpR2TiCl2). Addition of a substituted pentafulvene to alkyl/branched-alkyl/phenyl Grignard solutions with catalytic copper catalyst resulted in the formation of novel racemic/tautomeric cyclopentadienyl ligands in yields of up to 92%. The deprotonation of the racemic substituted cyclopentadienyl ligands with n-butyllithium and subsequent transmetallation with titanium(IV) tetrachloride resulted in the formation of novel substituted titanocene complexes in yields up to 81%. The antiproliferative activities of the (rac/meso)- mixtures of titanocenes in comparison to the simple benzyl-substituted titanocene analogue, titanocene dichloride and cisplatin were then evaluated in vitro against HCT-116, MiaPaCa-2 and MDA-MB-468 carcinoma cell lines, which represented intractable cancers from three different organ sites. All chiral substituted titanocenes were micromolar active against all the studied cancer cell lines. Finally, cyclic voltammetry studies using chiral substituted titanocenes were carried which confirmed a close to optimal fit of the chiral substituted ethyl titanocene.